Stilistika i ritorika v ih vzaimootnošenii - Kožina, Margarita N. (Stylistyka, 2000)
The article considers the question ofthe subject ofstylistics and rhetoric in their cor[1]relation. Similar and distinctive features ofthese disciplines are analyzed, i.e. the aims and purposes ofresearch, their extralinguistic foundations, and methods ofthe material research. Rhetoric is viewed as the integrated one in the complex of humanity studies of communication.